The fourteenth year - Zavadskas, Edmundas Kazimieras (Technological and Economic Development of Economy, 2008)
Editorial “The fourteenth year” Technological and Economic Development of Economy, 14(1), 5–7. Editor-in-chief Prof Edmundas Kazimieras Zavadskas First published online: 21 Oct 2010